If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1y) = 108forx (2x * 3 + -1y * 3) = 108forx (6x + -3y) = 108forx Solving 6x + -3y = 108forx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-108forx' to each side of the equation. 6x + -108forx + -3y = 108forx + -108forx Reorder the terms: -108forx + 6x + -3y = 108forx + -108forx Combine like terms: 108forx + -108forx = 0 -108forx + 6x + -3y = 0 Add '3y' to each side of the equation. -108forx + 6x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 -108forx + 6x + 0 = 0 + 3y -108forx + 6x = 0 + 3y Remove the zero: -108forx + 6x = 3y Combine like terms: 3y + -3y = 0 -108forx + 6x + -3y = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-36forx + 2x + -1y) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-36forx + 2x + -1y)' equal to zero and attempt to solve: Simplifying -36forx + 2x + -1y = 0 Solving -36forx + 2x + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. -36forx + 2x + -1y + y = 0 + y Combine like terms: -1y + y = 0 -36forx + 2x + 0 = 0 + y -36forx + 2x = 0 + y Remove the zero: -36forx + 2x = y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x^2-48x+540=0 | | (x/3)-2=2x-17 | | -35+9x=9+7x | | 3x-0y=27 | | 3x-2y-40=x+3y+20 | | -5d=6/-6 | | 4d+8=6d-4 | | lx-2l=x/3 | | 7(5x+8)=12-x-4 | | 5b-2c^2=3(b-2) | | 3x^2-16x+16=720 | | 2n(3n-4)=0 | | 7x+8a=124 | | -8(5x-6)= | | f(z)=z^2-2z | | 5z*3z= | | 32=x+7+3x+x+x+7+3x+x | | -61-3x=3x+34 | | 4(3x-1)=2(2x+7) | | -2/3(6x+7)=18 | | 9b+3-4b-10=3 | | 8y=5x+17 | | 3(2x+1)=5x-4 | | 16+2n=24 | | y-1.2=4/8 | | p(x+1)(x-3)=0 | | j^2+5j=-4 | | x^2+13x=-22 | | -31=8+-6p+-7p | | 25-x/7=2 | | TC=1000+8Q | | 72=1/2(4t^2) |